PETRONILHA BEATRIZ GONÇALVES E SILVA: PROFESSOR, RESEARCHER, POLITICAL-SOCIAL ACTIVIST - Canavarro Benite, Anna M. (Revista da Associação Brasileira de Pesquisadores/as Negros/as (ABPN), 2020)
Petronilha Beatriz Gonçalves e Silva was born in Porto Alegre, in the Colônia Africana neighborhood, at Rua Esperança, in 1942. She has a degree in Letters - Portuguese and French (1964), a Masters in Education (1979) and a PhD in Humanities - Education (1987) by the Federal University of Rio Grande do Sul. Petronilha retired in 2012, when she was awarded the title of Professor Emeritus at UFSCar. Furthermore, it promotes and develops actions for a high quality education and for the struggle for a tolerant, harmonious and unprejudiced coexistence in our society.